Relationship between Cluster of Differentiation 4 Levels and Neuroopthalmic Manifestations in HIV Patients in Haji Adam Malik General Hospital Medan - Sinaga, Sofi Oktaviera; Ritarwan, Kiking; Iqbal, Kiki Mohammad (Journal of Society Medicine, 2023)
Introduction: The neuroophthalmic manifestations of HIV infection involve afferent and efferent visual pathways. Neuroophthalmic involvement is caused by direct infection and opportunistic infections. Screening for neuroophthalmic manifestations should be done even without vision complaints to identify neuroophthalmic signs and symptoms and refer to a neuroophthalmologist soon. The aim of this study was to determine the relationship between CD4 levels and neuroophthalmic manifestations in HIV positive patients Method: It was a cross-sectional study with primary data sources taken consecutively from HIV positive patients at Haji Adam Malik General Hospital in Medan. Subjects were examined for CD4 levels and also performed the neuroophthalmic and neurological physical examination such as visual acuity examination, visual field, pupil examination and funduscopy. Results: There were 45 subjects with demographic characteristics the most of subjects were male (71.1%), age group 31-40 years (55.6%) with an average age of 35.98 + 9.23 years, self-employed (46.7%), married (60% ) and Bataknese (62.8%). CD4 levels < 200 cells/µL were found at 55.6% with a median value of 162 cells/µL (30-878). The most of neuroophthalmic clinical manifestations were found in 52% of subjects with CD4 levels <200 cells/µL with symptoms of blurred vision (22.2%) and clinical signs of abnormalities on fundoscopy (20%). There was a significant relationship between CD4 levels and neuroophthalmic manifestations in HIV patients (p<0.005). Conclusion: There was a significant relationship between CD4 levels and neuroophthalmic manifestations in HIV patients (p<0.005).